Colonoscopy vs. Fecal Immunochemical Test in Reducing Mortality From Colorectal Cancer (CONFIRM): Rationale for Study Design. (November 2017) - Dominitz, Jason A; Robertson, Douglas J; Ahnen, Dennis J; Allison, James E; Antonelli, Margaret; Boardman, Kathy D; Ciarleglio, Maria; Del Curto, Barbara J; Huang, Grant D; Imperiale, Thomas F; Larson, Meaghan F; Lieberman, David; et al.
Abstract : Rationale: Colorectal cancer (CRC) is preventable through screening, with colonoscopy and fecal occult blood testing comprising the two most commonly used screening tests. Given the differences in complexity, risk, and cost, it is important to understand these tests' comparative effectiveness. Study design: The CONFIRM Study is a large, pragmatic, multicenter, randomized, parallel group trial to compare screening with colonoscopy vs. the annual fecal immunochemical test (FIT) in 50, 000 average risk individuals. CONFIRM examines whether screening colonoscopy will be superior to a FIT‐based screening program in the prevention of CRC mortality measured over 10 years. Eligible individuals 50–75 years of age and due for CRC screening are recruited from 46 Veterans Affairs (VA) medical centers. Participants are randomized to either colonoscopy or annual FIT. Results of colonoscopy are managed as per usual care and study participants are assessed for complications. Participants testing FIT positive are referred for colonoscopy. Participants are surveyed annually to determine if they have undergone colonoscopy or been diagnosed with CRC. The primary endpoint is CRC mortality. The secondary endpoints are (1) CRC incidence (2) complications of screening colonoscopy, and (3) the association between colonoscopists' characteristics and neoplasia detection, complications and post‐colonoscopy CRC. CONFIRM leverages several key characteristics of the VA's integrated healthcare system, including a shared medical record with national databases, electronic CRC screening reminders, and a robust national research infrastructure with experience in conducting large‐scale clinical trials. When completed, CONFIRM will be the largest intervention trial conducted within the VA (ClinicalTrials.gov identifier: NCT01239082).